HUMANISTIC ISLAMIC EDUCATION AS A RESPONSE TO THE MORAL CRISIS AND PSYCHOLOGICAL DISORDERS OF ADOLESCENTS IN THE SOCIETY 5.0 ERA - Ahmad Rahmadani; Nurul Hidayah Putri; Miftahul Ulum (Karimiyah: Journal of Islamic Literature and Muslim Society, 2025)
The Society 5.0 era presents multidimensional challenges for the moral and psychological development of Indonesian Muslim adolescents, marked by accelerating digital addiction, the erosion of ethical values, and a surge in psychological disorders including anxiety and depression. This study aims to examine and develop the concept of Humanistic Islamic Education as a systematic and epistemologically grounded response to this crisis, drawing primarily on the thought of Syed Muhammad Naquib al-Attas concerning the Islamization of knowledge and the concept of taʼdib. Employing library research methodology with a critical-integrative analysis approach, this study examines the philosophical foundations of al-Attas’s educational thought, situates it within the contemporary Society 5.0 context, and develops a five-pillar operational model of Humanistic Islamic Education. The results demonstrate that Humanistic Islamic Education, anchored in the concepts of tauhid-as-episteme, taʼdib-as-methodology, insan kamil-as-telos, fitrah-as-point-of-departure, and tawazun-as-principle, constitutes a holistic pedagogical system capable of forming an integrated self-identity, cultivating psychological resilience, and providing a robust ethical foundation for adolescents navigating digital disruption. This model integrates spiritual (ruh), intellectual (ʻaql), and emotional (qalb) dimensions in a unified pedagogical framework, positioning itself as a substantive antithesis to the secular reductionism that dominates global education systems.